Refugee Organizations’ Public Communication: Conceptualizing and Exploring New Avenues for an Underdeveloped Research Subject - Ongenaert, David (2019)
The world has faced a major increase in forced displacement and the theme has also become the subject of many public, media and political debates. The public communication of refugee organizations thereby increasingly impacts their operations, the public perception on forcibly displaced people and societal and policy beliefs and actions. However, little research has been conducted on the topic. Therefore, this conceptual article aims to (1) define refugee organizations’ public communication, (2) situate it within broader research fields, and (3) motivate the latter’s relevance as research perspectives. In order to be able to achieve these research objectives, the article first discusses the social and scientific relevance of the research subject and identifies important gaps within literature which both form an essential scientific base for developing the main arguments. Adopting a historical perspective, the article demonstrates that in recent decades the social and scientific relevance of research on strategic and non-profit communication in general and on refugee organizations’ public communication in particular have increased. Nevertheless, these fields remain underdeveloped and are mostly text-focused, while the production and reception dimensions are barely explored. Remarkably, however, little or no research has been conducted from an organizational communication perspective, although this article demonstrates that the subject can be adequately embedded in and examined from the fields of strategic, non-profit and public communication. Finally, the article highlights the relevance of the holistic Communicative Constitution of Organizations perspective and argues that future research can benefit by adopting multi-perspective, practice-oriented, multi-methodological, comparative and/or interdisciplinary approaches.